Epidemiological characteristics and distribution of congenital thumb duplication in south China: An analysis of 2,300 thumbs in 2,108 children - Wu, JianPing; Shi, WeiZhe; Lin, XueMei; Li, JingChun; Yuan, Zhe; Zhu, Mingwei; Liu, YuanZhong; Li, YiQiang; Canavese, Federico; Xu, HongWen (Frontiers in Pediatrics, 2022)
Objective The objective of this study was to evaluate epidemiological and anatomical characteristics of children with congenital thumb duplication (CTD). Methods We retrospectively reviewed 2108 children with CTD. Data regarding sex, age at the surgery, laterality, uni- or bilateral involvement, and dominant side were retrieved from the medical charts. Plain radiographs were used to classify all CTD according to Wassel-Flatt, Rotterdam and Chung classification systems and to evaluate the patho-anatomy of the duplication as well as the presence of associated anomaly. Results A total of 796 girls and 1,312 boys with CTD (n = 2,300 thumbs) met the inclusion criteria. The male to female and unilateral to bilateral ratio were 1.6:1 and 10:1, respectively. Associated anomaly was found in 238/2108 patients (11.3%), and the middle phalanx deformity of the 5th finger was the most common one. A dominant thumb, larger and more developed, was on the ulnar side in 2270/2,300 cases (98.7%). According to the Wassel-Flatt classification, type IV (40.2%) was the most common deformity and the extra thumb was connected to the main thumb by a joint in most cases (437/780); overall, 15.7% of thumbs (n = 360) did not fit the Wassel-Flatt classification. According to the Rotterdam classification, type IV (51.3%) was the most common form; in most cases (363/1180) the thumb was hypoplastic or floating. Overall, 3/2,300 thumbs (0.1%) could not be classified according to Rotterdam classification. According to the Chung classification, type A was the most common subtype (44.1%); in most cases (716/1015) the duplication was at the level of the metacarpal bone. Overall, 2/2,300 thumbs (0.1%) did not fit the Chung classification. Conclusions In patients from southern China, CTD shows male and right-sided predominance with ulnar-dominant thumb. Abnormalities of the middle phalanx of the 5th finger are more frequent in patients with associated anomaly. The development of a simple and comprehensive classification system is needed to guide treatment and to adequately assess the epidemiological characteristics of patients with CTD in order to facilitate comparison between different patients' populations. Level of evidence III